Anti-Obesity Effects of Sulphated Polysaccharides Derived from Marine Macro Algae or Seaweeds: A Systematic Review and Meta-Analysis - S’thandiwe Nozibusiso Magwaza; Vunene Nkateko Chabalala; Nothando Philile Hlongwane; Huda Ismail; Md. Shahidul Islam (Marine Drugs, 2024)
Sulphated polysaccharides (SPs) are negatively charged compounds found in the cell wall of seaweeds or marine macro algae. These compounds exhibit a range of pharmacological activities, including anti-obesity effects. The aim of this systematic review as well as meta-analysis was to assess the potentials of seaweed-derived SPs to mitigate obesity through a systematic review and meta-analysis of animal model-based studies. A comprehensive summary of the included articles was conducted, focusing on the following obesity-related parameters: food intake, body weight gain, epididymal fat size, adipocyte size, liver weight, serum alanine transaminase (ALT) and aspartate transaminase (AST), insulin and tumour necrosis factor-α (TNF-α), and the lipid profile (total cholesterol, triglyceride, high-density lipoprotein cholesterol (HDL-c), and low-density lipoprotein cholesterol (LDL-c)). The systematic review demonstrated that seaweed-derived SPs exhibit ameliorative effects against obesity, as evidenced by reductions in food intake, body weight gain, epididymal fat and adipocyte size, liver weight, ALT and AST levels, serum insulin and TNF-α, LDL-c, total cholesterol, and triglycerides and an increase in HDL-c in obese rats administered with seaweed-derived SPs. However, the meta-analysis revealed statistically significant anti-obesity effects of seaweed-derived SPs for most, but not all the parameters tested. Further research in human subjects is necessary not only to ascertain the results of preclinical studies but also to provide conclusive evidence of the anti-obesity potential of SPs in humans.